Association between the dietary index for gut microbiota and osteoporosis among middle-aged and older adults in the United States - Yiming Zhan; Yuhang Liu; Jialing Tang; Siyao Gao (Preventive Medicine Reports)
Objective: Osteoporosis is an age-related disease, and the gut microbiota plays a crucial role in regulating bone mineral density (BMD) through modulating nutrient absorption, immunity, and bone metabolism. This research examines the association between the dietary index for gut microbiota (DI-GM) and osteoporosis prevalence among US middle-aged and older adults.Methods: We included 7255 middle-aged and elderly adults from the National Health and Nutrition Examination Survey (NHANES) 2007–2020. The DI-GM was calculated based on 14 dietary components associated with gut microbiota health. Osteoporosis was defined by femoral neck BMD T-score ≤ −2.5. Multivariable logistic regression and restricted cubic spline (RCS) models were employed to examine the relationship between DI-GM and osteoporosis.Results: Higher DI-GM scores were significantly and negatively associated with the prevalence of osteoporosis (odds ratio [OR] = 0.91, 95 % CI = 0.85–0.97), and a nonlinear trend was observed. Additionally, a higher beneficial component score of DI-GM was associated with a lower incidence of osteoporosis (OR = 0.85, 95 % CI = 0.78, 0.92). Sensitivity analyses further confirmed the robustness of these findings.Conclusions: Higher DI-GM scores were significantly and nonlinearly associated with a lower prevalence of osteoporosis. Future research should validate these findings through longitudinal studies.